Glucose Metabolism in Sheep Fed Grass Supplemented with Gliricidia Sepium - Y. Widiawati; E. Teleni; Suharyono Suharyono (PPIKSN-BATAN, 2014)
The limiting factor on improving ruminant production for most of the available feed in developing countries are low in quality. Therefore high fibre diet must be supplemented by high nutritivefeed such as leguminous trees that much available in those regions. Gliricidia sepium was one of very potential candidates. Glucose as a major energy source in fed animals required precursor in form of propionat and amino acids from diet. Those precursors might be supplied by these legume leaves. The aim of this research was to investigate the glucose metabolism in the sheep fed grass supplemented by Gliricidia sepium. Fifteen sheeps (18 months old) were used in the experiment. Theseare were divided into three groups that fed by experimental diet of Mitchell grass (MG group), Gliricidia(GS group), and MG supplemented with GS (MGGS group). D-[U-14C]glucoseinfusate was infused continuously through the left jugular venous catheter of each animal to measure glucose metabolism in those sheeps. The measurements were done on feed utilisation and glucose metabolism. The results indicated that there was an improvement in efficiency of feed utilisation in the MGGS group as reflected by lower feed conversion ratio by the group. Plasma glucose concentration profile per unit of OM intake were similar for GS and MGGS groups, but higher than that in the MG group (P<0.01). Glucose entry rate (GER) increased in MG group through GS to the MGGS group, while N retention accordingly was increased. It can be concluded that theutilization of GS by the ruminant animal could be improved by feeding it with a low quality feed at a ratio of 40:60 (GS:Low quality feed) to achieve an NI:DOMI ratio of 0.03 - 0.04. This improvement would be manifested in increasing DOMI, with subsequent increase in GER or net protein deposition as might be expressed in positive N retention. Received: 8 October 2014; Revised: 12 December 2014; Accepted: 24 December 2014